Pengaruh Struktur Aktiva, Struktur Modal, dan Perputaran modal Kerja terhadap Kinerja Keuangan pada PT Astra International Tbk periode tahun 2010-2025 - Bonefasius Dayung; Fazhar Sumantri; Theysa Shalani Pratiwi (Universitas Veteran Bangun Nusantara, 2026)
PT Astra International Tbk operates in the trading, services, and automotive industries. This study aims to examine the effect of Asset Structure, Capital Structure, and Working Capital Turnover on Financial Performance, measured by Return on Assets (ROA), at PT Astra International Tbk during the 2010–2025 period. The research employed a quantitative method using multiple linear regression analysis with SPSS version 20. The sample was determined through purposive sampling using a saturated sampling method based on the company's financial statements over a 16-year period. Secondary data were obtained from books, scientific journals, and published financial reports. The partial test results indicate that Asset Structure (t-value = -1.430; significance = 0.178 > 0.05), Capital Structure (t-value = 1.569; significance = 0.143 > 0.05), and Working Capital Turnover (t-value = 1.150; significance = 0.273 > 0.05) do not have a significant effect on financial performance. Simultaneously, the F-test results show that the calculated F-value of 3.222 is lower than the F-table value of 3.490, with a significance level of 0.061 > 0.05. These findings demonstrate that the three independent variables, both individually and collectively, do not have a significant effect on the financial performance of PT Astra International Tbk. These findings confirm that Asset Structure, Capital Structure, and Working Capital Turnover are not the primary factors influencing the financial performance of PT Astra International Tbk. Therefore, the company should focus on optimizing other more dominant factors to enhance profitability and achieve sustainable financial performance.